Preference of Students on the Format of Options in a Multiple-Choice Test - Voltaire Quiza Oyzon; Hermabeth O. Bendulo; Erlinda D. Tibus; Rhodora A. Bande; Myrna L. Macalinao (Institute of Advanced Engineering and Science, 2016)
Schools in the Philippines, especially those that are offering teacher education programs, are advised to construct examinations that are Licensure Examination for Teachers (LET)-like test items. This is because “if any aspect of a test is unfamiliar to candidates, they are likely to perform less well than they would do otherwise on subsequently taking a parallel version, for example.” Using the education students of Leyte Normal University, Southern Leyte State University-Tomas Oppus Campus, and Visayas State University, this study determined the students’ preference on the arrangements/format of options in a multiple-choice test through a survey questionnaire. Moreover, it tried to find out the reasons behind the preferences. Mean, frequency and Chi-square tests were used in the analysis of data. Results revealed that the cascading arrangement is the most preferred arrangement of options and the one-line horizontal arrangement is the least preferred arrangement of options in a multiple-choice test. The reasons identified were organized and easy to read, less confusing and easier to distinguish and vertically arranged thus require less eye movement. Moreover, the reasons for the lower case preference were it is usual and commonly used in a multiple-choice test, clear and gives less eye and mental pressure and easier to read and write.And lastly, the relationship between the students’ preference of the arrangement of options in a multiplechoice test and the letter case options were tested using the Chi-square test. Hence, it is argued that in constructing a multiple-choice test, one has to consider using the cascading arrangement.